Femtosecond Laser-Induced Photothermal Effects of Ultrasmall Plasmonic Gold Nanoparticles on the Viability of Human Hepatocellular Carcinoma HepG2 Cells - Poornima Budime Santhosh; Kamelia Hristova-Panusheva; Todor Petrov; Lyubomir Stoychev; Natalia Krasteva; Julia Genova (Cells)
Laser-induced photothermal therapy using gold nanoparticles (AuNPs) has emerged as a promising approach to cancer therapy. However, optimizing various laser parameters is critical for enhancing the photothermal conversion efficacy of plasmonic nanomaterials. In this regard, the present study investigates the photothermal effects of dodecanethiol-stabilized hydrophobic ultrasmall spherical AuNPs (TEM size 2.2 ± 1.1 nm), induced by a 343 nm wavelength ultrafast femtosecond-pulse laser with a low intensity (0.1 W/cm2) for 5 and 10 min, on the cell morphology and viability of human hepatocellular carcinoma (HepG2) cells treated in vitro. The optical microscopy images showed considerable alteration in the overall morphology of the cells treated with AuNPs and irradiated with laser light. Infrared thermometer measurements showed that the temperature of the cell medium treated with AuNPs and exposed to the laser increased steadily from 22 °C to 46 °C and 48.5 °C after 5 and 10 min, respectively. The WST-1 assay results showed a significant reduction in cell viability, demonstrating a synergistic therapeutic effect of the femtosecond laser and AuNPs on HepG2 cells. The obtained results pave the way to design a less expensive, effective, and minimally invasive photothermal approach to treat cancers with reduced side effects.